Key to genera of Chinese Coelidiinae leafhoppers, with description a new species of the leafhopper genus Baseprocessa (Hemiptera: Auchenorrhyncha: Cicadellidae) - Wang, Xian-Yi; Fan, Zhi-Hua; Li, Zi-Zhong; Dai, Ren-Huai (Zootaxa, 2019)
The genus Baseprocessa Fan & Li, 2017 is reviewed and a new species B. longiprocessa sp. nov. from Tibet is described and illustrated. An updated checklist and distributions of the species of this genus are provided and a key to Chinese Coelidiinae genera is included.